An Experimental Investigation on the Air Permeability of Passive Ventilation Grilles. (November 2015) - Alfano, F.R. d'Ambrosio; Ficco, G.; Palella, B.I.; Riccio, G.; Ranesi, A.
Abstract: The need of increasing both energy saving and acoustic insulation has leaded to the design of lowest air permeability frames resulting in the worsening of indoor air quality. Moreover, sometime in several civil-use existing buildings (i.e. schools or houses, historical buildings) mechanical ventilation systems cannot be installed due to non-removable constraints. In these cases, passive ventilation grilles are a cheap and effective solution for the ventilation. This work deals with an in-depth experimental analysis about the air permeability values measured over a set of passive ventilation grilles available on the market. Obtained results often showed performances very far to those declared. This is not due to multiplicity of involved parameters affecting their behaviour rather to a lack of standardized test methods.